Local immunity features in patients with non-invasive muscular bladder cancer of various degrees of malignance - A. B. Sagakyants; L. I. Belyakova; A. N. Shevchenko; E. S. Bondarenko; E. Yu. Zlatnik; I. A. Novikova; E. V. Filatova; V. K. Hvan; I. A. Khomutenko; D. V. Burtsev (Южно-Российский онкологический журнал)
Purpose of the study. To study the features of the local distribution of populations of immune system cells in patients with non-invasive muscular bladder cancer of various degrees of malignancy.Materials and methods. The study included 51 patients with newly diagnosed non-muscle-invasive bladder cancer (papillary urothelial carcinoma) who received complex treatment and follow-up after 9 months at the oncourological department of the National Medical Research Center of Oncology. Patients were divided into two groups: group 1 – with a tumor of low malignant potential (Low grade – LG), n = 31; group 2 – with a tumor of high malignant potential (High grade – HG), n = 20. After 6–9 months, 24 patients were diagnosed with a relapse of the disease – in 48,4 % in patients of group 1 (n = 15) and in 45 % – in group 2 (n = 9). In cell suspensions obtained from the primary and recurrent tumors, as well as the perifocal zone, the relative number of populations of immunocompetent cells was estimated using flow cytometry. A comparison was made of the content of individual populations of lymphocytes in the tumor tissue, the perifocal zone of primary and recurrent lesions of various degrees of malignancy. Statistical processing was performed using Statistica 13.0.Results. The development of a recurrent tumor of low malignant potential is accompanied by the involvement of cells of innate immunity (NK- and NKT-lymphocytes) into its microenvironment, which is associated with an imbalance in the number of main cells of adaptive immunity – a fairly pronounced decrease in the tumor of T-lymphocytes of the helper-inductor type was noted with a constant content cytotoxic T-lymphocytes, as well as the multidirectional nature of changes in DP- (decrease) and DN-lymphocytes (increase). A feature of the development of a recurrent tumor of high malignant potential is that it is accompanied by the involvement of innate immunity cells (NK- and NKT-lymphocytes) into its microenvironment, as well as multidirectional changes in DP- (decrease) and DN-lymphocytes (increase).Conclusion. Studies of the population composition of tumors and their perifocal tissues of NMIBC revealed a number of features that are reflected in the redistribution of cytolytic cells, the formation of immunosuppressive conditions, which are reflected both in the manifestation of the biological properties of tumor cells and in changes in the cellular composition of bladder tissues involved in the process. development and progression of cancer.